Exogenous retroelement integration in sperm and embryos affects preimplantation development. Issue 3 (September 2016) - Kitsou, C; Lazaros, L; Bellou, S; Vartholomatos, G; Sakaloglou, P; Hatzi, E; Markoula, S; Zikopoulos, K; Tzavaras, T; Georgiou, I
Abstract : Retroelement transcripts are present in male and female gametes, where they are typically regulated by methylation, noncoding RNAs and transcription factors. Such transcripts are required for occurrence of retrotransposition events, while failure of retrotransposition control may exert negative effects on cellular function and proliferation. In order to investigate the occurrence of retrotransposition events in mouse epididymal spermatozoa and to address the impact of uncontrolled retroelement RNA expression in early preimplantation embryos, we performed in vitro fertilization experiments using spermatozoa preincubated with plasmid vectors containing the human retroelements LINE-1, HERVK-10 or the mouse retroelement VL30, tagged with an enhanced green fluorescence (EGFP) gene-based cassette. Retrotransposition events in mouse spermatozoa and embryos were detected using PCR, FACS analysis and confocal microscopy. Our findings show that: (i) sperm cell incorporates exogenous retroelements and favors retrotransposition events, (ii) the inhibition of spermatozoa reverse transcriptase can decrease the retrotransposition frequency in sperm cells, (iii) spermatozoa can transfer exogenous human or mouse retroelements to the oocyte during fertilization and (iv) retroelement RNA overexpression affects embryo morphology and impairs preimplantation development. These findings suggest that the integration of exogenous retroelements in the sperm genome, as well as their transfer into the mouse oocyte, could give rise to new retrotransposition events and genetic alterations in mouse spermatozoa and embryos.